The Career choices of Internal Medicine Residents of the University of the Philippines-Philippine General Hospital - Fernando, Gracieux Y. (2003)
This study was conducted to examine the career choices of internal medicine residents at the University of the Philippines-Philippine General Hospital (UP-PGH), including the different factors that influenced these decisions. By looking into the career choices of internal medicine residents of the UP-PGH, it was hypothesized that, quite possibly, the choices they made were influenced by factors that were within the realm of influence by the medical training program. To answer these concerns, a descriptive, cross sectional study was developed. In order to gather the needed data, a survey questionnaire was developed in which medical residents were asked to select their future career choices, rank the different subspecialties of the internal medicine department, and rate the different factors that influence these career decisions. The questionnaire was developed through literature research, which helped generate a list of possible factors. This list, in turn, was further narrowed down to what was applicable to the current environment of the Department of Internal Medicine, UP-PGH, through interviews with key informants like residents, fellows, and consultants of the department. It was then pre-tested on a similar group of internal medicine residents in a different training institution for ease of utilization and clarity. The revised tool was then administered to 60 residents of the Department of Internal Medicine, UP-PGH. Descriptive statistics were utilized to describe demographics of respondents, career choices, including place of practice and activities involved in during practice, subspecialty preferences, degree of factor influence, and rank of general factor categories. Kruskal-Wallis analysis of variance was conducted to determine whether there was variation in responses across various year levels of training and other demographic factors. Of the 60 targeted respondents, 57 (93.2%) returned completed survey forms. Male to female ratio of respondents was 1.1:1. The results show that internal medicine residents of UP-PGH have an average age of 28 years, most likely single, have a more than 50% chance of having one or more relatives who are also doctors. In more than 85% of cases, these residents plan to go into fellowship training after residency. Upon completion of training, they reported to plan to practice in Metro Manila and get involved in both clinical and hospital based practice in 85% of the time. However, only 50% are interested in teaching and only 30% would continue research, most of these being male. A look at the factors that influence these choices show that they value highly intellectual fulfillment and personal interest as influencing factor. Additional influences involved several training-related factors, in particular, their exposure to role models and to the different patients that they have handled. This intellectual need is tempered by their humanitarian aspects, reflected in the value they place in service to others, particularly the underprivileged. Yet despite these, the residents remain grounded in reality, recognizing the important influence that economic needs play on any career choice. These important factors, however, remain deeply personal and a part of the individual's background and value system. Because they are inherent to the individual, moves to modify the training program may be unsuccessful unless they deal with values exposure, clarification, or development. Should the training program look to influence the future career choices of its medicine residents, however, it would have two very important tools at its disposal: the consultant staff, which serve as role models, and the variety of patients encountered during their training, which can help fuel their intellectual curiosity.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Career Choice